Fluctuating thermal regimes extend longevity and maintain fecundity to increase shelf‐life of Drosophila melanogaster cultures. (2nd May 2021) - Melicher, Dacotah; Wilson, Amanda M.; Yocum, George D.; Rinehart, Joseph P.
Abstract: Reduced temperatures increase longevity in cold‐tolerant insects, but insects that are not cold‐tolerant experience elevated mortality at constant low temperatures. Fluctuating thermal regimes (FTRs) increase longevity in many insect species while slowing or delaying development and senescence. Under FTR insects are held at low temperature with a daily warm pulse of increased temperature. The model organism Drosophila melanogaster is widely used for diverse research activities and numerous transgenic strains have been developed and must be maintained in continuous culture at stock centres. We measured the effect of FTR that oscillates between 6 and 22 °C on the longevity and fertility of adult D . melanogaster versus a constant temperature of 6 and 22 °C. We demonstrate that FTR increases mean longevity by 8.8‐fold compared to a constant 6 °C and by 5.9‐fold to a constant 22 °C. We assessed male and female fertility of FTR treated adults from 20 to 100 days at 20 day intervals and constant temperature treated adults after 7 days. Under FTR males exhibited increased fertility peaking at 80 days before dropping significantly at 100 days. Mean female fertility declined steadily under FTR but remained at 53% of constant temperature‐treated flies after 60 days. The increased male fertility remains unexplained. Fertility of the offspring of FTR‐treated adults did not differ from flies reared at constant 22 °C. FTR extends generations and cultures incubated under this protocol can establish new cultures. FTR can be used to further investigate the accumulation and mitigation of chill injury and is suitable for reducing maintenance in stock centres. Abstract : Fluctuating thermal regimes extended generation time while maintaining fertility. Fluctuating thermal regimes increased longevity of Drosophila melanogaster to a mean of 152 days. Male fecundity increased slightly over 80 days before decreasing. Female fecundity was stable for 60 days before decreasing due to infertile females.